Management and Treatment of External Hemorrhoidal Thrombosis - Picciariello, Arcangelo; Rinaldi, Marcella; Grossi, Ugo; Verre, Luigi; De Fazio, Michele; Dezi, Agnese; Tomasicchio, Giovanni; Altomare, Donato F; Gallo, Gaetano (Frontiers in Surgery, 2022)
Background External hemorrhoidal thrombosis (EHT) is a common complication of hemorrhoidal disease. This condition causes extreme pain, likely resulting from internal anal sphincter hypertonicity, which traps the hemorrhoids below the dentate line thus leading to congestion and swelling. The choice of treatment remains controversial and both conservative and surgical options have been proposed in the last decades. Methods This mini-review focuses on the most relevant studies found in literature evaluating conservative and surgical management of EHT. Special conditions such as pregnancy and EHT in elderly patients have been considered. Results Traditionally, symptoms duration represents the discriminant in the choice between medical and surgical treatment. Several Coloproctological Societies considered conservative treatment as the first-line approach to EHT and a variety of options have been proposed: wait and see, mixture of flavonoids, mix of lidocaine and nifedipine, botulinum toxin injection and topical application of 0.2% glyceryl trinitrate. Meanwhile, different surgical treatments are recommended when EHT fails to respond to conservative management or when symptoms onset falls within the last 48–72 h: drainage with radial incision, conventional excision, excision under local anesthesia and stapled technique. Conclusion The management and treatment of EHT is still controversial since no specific guidelines have been published. Both medical and surgical treatment have been proven effective but randomized clinical trials and structured consensus-based guidelines are warranted.